Pengaruh Tingkat Pendidikan, Masa Kerja Dan Komitmen Terhadap Kinerja Karyawan Di Radio Republik Indonesia Kota Malang - Rachmaudinah Hilda Safitri; Rois Arifin; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to determine the effect of education level, tenure and commitment to employee performance at Radio Republik Indonesia Malang City. The sample in this study amounted to 75 respondents who are employees of Radio Republik Indonesia Malang City. The sampling technique used was saturated sampling or census. The data used in this study used primary data and secondary data obtained from the distribution of questionnaires to employees of Radio Republik Indonesia Malang City. The method used is data analysis with validity, reliability, normality, multicollinearity test, heteroscedasticity test, multiple regression analysis test, f test, t test and coefficient of determination. With the results of the study showed that simultaneously the level of education, tenure, commitment affect employee performance, while partially education level, tenure, commitment affect employee performance at Radio Republik Indonesia Malang City. Kata kunci : Tingkat Pendidikan, Masa Kerja, Komitmen, Kinerja Karyawan